1980
DOI: 10.3109/00048678009159369
|View full text |Cite
|
Sign up to set email alerts
|

Female Transsexualism in Singapore: A Report on 20 Cases

Abstract: Twenty female transsexuals were assessed for sexual reassignment surgery in Singapore. This gives a prevalence of 1 in 36,000 for females aged 15 and above. The age ranged from 18 to 31 with the mean at 24.9 years. Fifteen had received secondary education and 19 were employed. There was no history of serious anti-social behaviour. They were closer to their mothers, some of whom encouraged their cross dressing behaviour during childhood. Their behaviour became more masculine as they grew older. All were unmarri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Four studies (Tsoi et al, 1977;Tsoi and Kok, 1980;Tsoi and Peng, 1995;Fang, 1994) have reported the clinical and psychological characteristics of transsexuals. Ng et al (1989) Carpenter and Treacher, 1993) has been adopted to conceptualize their problems.…”
Section: Joyce L C Mamentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies (Tsoi et al, 1977;Tsoi and Kok, 1980;Tsoi and Peng, 1995;Fang, 1994) have reported the clinical and psychological characteristics of transsexuals. Ng et al (1989) Carpenter and Treacher, 1993) has been adopted to conceptualize their problems.…”
Section: Joyce L C Mamentioning
confidence: 99%
“…The experience of transsexuals in Asia has been documented (Tsoi et al, 1977;Tsoi and Kok, 1980;Tsoi and Peng, 1995;Wen 1979;Ma, 1989;1990;Ng et al, 1989;Fang, 1994). Four studies (Tsoi et al, 1977;Tsoi and Kok, 1980;Tsoi and Peng, 1995;Fang, 1994) have reported the clinical and psychological characteristics of transsexuals. Ng et al (1989) have described the comprehensive care provided by the Gender Identity Team in Hong Kong, while Working with transsexuals in Hong Kong 73 Ma (1990) developed criteria for evaluating their role performance during the 'trial' period.…”
mentioning
confidence: 99%